Analysis of Network Attached Storage Performance with NFS Protocol in Integrated Business Start-Up - Barovih, Guntoro; Surahmat, Surahmat; Febrianty, Febrianty (Sinkron : jurnal dan penelitian teknik informatika, 2023)
The need for data storage due to individual and group computing work is increasing, so storage media with reliable capabilities and good performance are needed. The way that can be solution is shared storage, which is using one storage to be used together. One of the commonly used shared storage is NAS (Network Attached Storage). IBS (Integrated Business Start Up) uses NAS as a backup storage medium that will store important data that supports the performance of IBS services as a whole, so it is necessary to analyze to find out how the performance of the NAS system uses the NFS Protocol as the basis of the service. whereas in this study the focus of performance testing was carried out by looking at the results of measuring packet loss, throughput, CPU usage, and memory usage on the NAS server used. the performance level of the system used is running well, as seen from the results of the throughput test of 1.1 GB, packet loss of around 0%, CPU usage of 0.5%, and memory usage of 382.5Mb. The results of this performance test are also by Telecommunications standards and Internet Protocol Harmonization Through Networks